Performance of cluster-based cognitive multihop networks under joint impact of hardware noises and non-identical primary co-channel interference - Pham Minh Nam; Tran Trung Duy; Phan Van Ca (Universitas Ahmad Dahlan, 2019)
In this paper, we evaluate outage probability (OP) of a cluster-based multi-hop protocol operating on an underlay cognitive radio (CR) mode. The primary network consists of multiple independent transmit/receive pairs, and the primary transmitters seriously cause co-channel interference (CCI) to the secondary receivers. To improve the outage performance for the secondary network under the joint impact of the CCI and hardware imperfection, we employ the best relay selection at each hop. Moreover, the destination is equipped with multiple antennas and uses the selection combining (SC) technique to enhance the reliability of the data transmission at the last hop. For performance evaluation, we first derive an exact formula of OP for the primary network which is used to calculate the transmit power of the secondary transmitters. Next, an exact closed-form expression of the end-to-end OP for the secondary network is derived over Rayleigh fading channels. We then perform Monte-Carlo simulations to validate the derivations. The results present that the CCI caused by the primary operations significantly impacts on the outage performance of the secondary network.